Socialization and Education of Hadiths About Pandemics for The People of Karawang Regency - Debibik Nabilatul Fauziah; Yayat Herdiana; Yuna Tresna Wahyuna; Oyoh Bariah (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
This devotion is motivated by the current disaster that occurred, namely the covid 19 pandemic that hit almost all countries in the world including Indonesia. Karawang as one of the regencies in West Java Province is in the red zone position of the Covid 19 spreading case. In order to provide awareness to the public of the importance of complying with 5 M in accordance with the government's advice to reduce the number of Covid 19 spread in Karawang, the focus of this service is to provide educational information on the community in the form of socialization and education of hadiths about the pandemic against mothers of jama'ah majlis ta'lim Miftahul Jannah located in Krajan Hamlet Cilamaya Village Cilamaya District Cilamaya Wetan Karawang Regency. Given the role of mothers as the vanguard to educate families at home will be important to comply with health protocols set by the government. The implementation of this devotional activity uses the method of lectures by teaching hadiths about the plague to the community. The result of this devotion is to enlighten the community about Islamic solutions during the outbreak based on the hadith of the Prophet (peace be upon him)